Help an Ong: sistema de doações para instituições filantrópicas - CARVALHO, Joaquim Gabriel Pires de; SOUZA, Letícia Oliveira de; REIS, Luiz Kauan Orfao da Silva; NAZARÉ, Maria Julia da Silva; MARCOS, Maria Laura de Oliveira; FERREIRA, Victor Hugo Diniz (240, 2023)
"Help an ONG" é um sistema que visa melhorar a interação entre instituições filantrópicas e doadores em Lorena, São Paulo, enfrentando desafios relacionados à falta de doações e desconfiança na região. O protótipo simplifica o processo de doação por meio de um site, tornando-o mais acessível e seguro para os doadores. A ideia é impulsionar a arrecadação das instituições, promovendo um impacto social mais significativo. Espera-se que essa plataforma dinamize a relação entre doadores e instituições, facilitando um aumento nas doações.

"Help an ONG" is the name given to the concept of an interaction system between philanthropic institutions and donors in the city of Lorena, located in the state of São Paulo, as there are challenges related to the lack of donations and distrust in the donation process in the region. The prototype aims to facilitate and make it more accessible for users to make donations through a website, so that the donor feels more comfortable and secure with their donation. The idea of a portal for making donations can help institutions increase their fundraising, potentially making a greater impact on society. Through this, it is hoped that the relationship between donors and institutions can become more confident, improved, and dynamic, enabling a greater number of donations to registered institutions.
Help an Ong: donation System for philanthropic institutions
Keywords: Filantropia; Instituições sociais; Doação; Informação e Comunicação